THE CONCEPT OF CORRUPTION AND THE CONDITIONS AND FACTORS THAT CAUSE IT - Nazarov Shavkat Nazarovich (International Journal of Business, Law and Political Science, 2025)
Objective: This study aims to examine the concept of corruption, identify key factors contributing to its existence, and analyze its negative consequences on society. By understanding these aspects, the research seeks to provide a structured framework for addressing corruption effectively. Method: A comprehensive analysis was conducted by reviewing existing literature on corruption, focusing on its systemic, cultural, and economic causes. The study categorizes corruption’s root causes and assesses its impact on governance, economic stability, and social equity. Result: The findings indicate that economic disparity, weak legal frameworks, lack of transparency, and institutional inefficiencies are the primary drivers of corruption. These factors collectively undermine governance, weaken public trust, and hinder economic growth. The study also highlights the far-reaching consequences of corruption, including reduced public services, increased inequality, and political instability. Novelty: This study offers a structured approach to analyzing corruption by systematically categorizing its causes and consequences. Unlike previous research, it provides a more integrated perspective that connects corruption’s root causes to its broader socio-economic effects. The study also suggests targeted mitigation strategies, emphasizing the role of legal reforms, institutional transparency, and public awareness in combating corruption.